A conceptual framework for analysing and measuring land-use intensity - Karl-Heinz Erb; Helmut Haberl; Martin Rudbeck Jepsen; Tobias Kuemmerle; Marcus Lindner; Daniel Müller; Peter H Verburg; Anette Reenberg (Current Opinion in Environmental Sustainability, 2013)
Large knowledge gaps currently exist that limit our ability to understand and characterise dynamics and patterns of land-use intensity: in particular, a comprehensive conceptual framework and a system of measurement are lacking. This situation hampers the development of a sound understanding of the mechanisms, determinants, and constraints underlying changes in land-use intensity. On the basis of a review of approaches for studying land-use intensity, we propose a conceptual framework to quantify and analyse land-use intensity. This framework integrates three dimensions: (a) input intensity, (b) output intensity, and (c) the associated system-level impacts of land-based production (e.g. changes in carbon storage or biodiversity). The systematic development of indicators across these dimensions would provide opportunities for the systematic analyses of the trade-offs, synergies and opportunity costs of land-use intensification strategies.
Keywords: 330